Cranial MR Imaging in Neurofibromatosis - Bognanno, James R.; Edwards, Mary K.; Lee, Theodore A.; Dunn, David W.; Roos, Karen L.; Klatte, Eugene C. (American Journal of Neuroradiology, 1988)
Cranial MR images of 53 patients with neurofibromatosis were reviewed to determine the nature, extent, and number of intracranial abnormalities present. All patients studied met tentative definitions established for the diagnosis of neurofibromatosis. Twenty-three were scanned for evaluation of known CNS or cranial nerve involvement; the remainder were neurologically asymptomatic patients without suspected lesions referred for screening. Single lesions were noted in 32 patients. Multiple lesions were identified in 14 patients. Seven had normal scans. In 23 patients small focal areas of increased signal on T2-weighted scans within the brain were thought to represent heterotopias. Eight patients had chiasma I gliomas and two had optic nerve gliomas. Nine patients had parenchymal gliomas, two had ischemic changes, and one had a colloid cyst. Extraaxial lesions included acoustic neuromas (five patients), meningiomas (four), trigeminal neurofibromas (one), and dysplasia of a sphenoid wing (two). Of the 30 asymptomatic patients referred for screening, lesions were found in 23. MR was found to be an excellent method of imaging known disease and of detecting lesions in asymptomatic patients. Because of the large number of asymptomatic lesions detected in this population, a screening MR study is recommended in patients with neurofibromatosis.